A part of the Ottoman centralization policy: Travel permits and their samples until the 20th century - Ergün, Cengiz (Études sur la Région Méditerranéenne, 2020)
After the disappearance of feudality and the development of central governments, from the 16th century onwards, states wanted to control the movements of their citizens by several documents. These documents were a kind of passports, which were also used as identity documents, and their arrangements varied from country to country. With the undisputed triumph of capitalism and nation-state in 19th century Europe, the state’s control over the people was predominantly considered as an internal matter. Competition between states in the economic and military fields revealed the importance of centralization. Statesmen, who wanted to take advantage of this competition, went on to increase control over the activities of their populations. In the Ottoman Empire, the state-control over the movements of its citizens dates back well before the 19th century. Due to the manorial system in the Ottomans, the peasantry remained attached to their lands and the State imposed criminal sanctions on those who left their lands. There were serious migration waves to Western Anatolia and especially to Constantinople until the 20th century, and therefore it was necessary to prevent the entry of beggars and unemployed people without guarantees to the city. The obligation to have “yol hükmü” (road provision), whose name was changed to “mürur tezkeresi” (passing compass), was also one of these considerations. In this study, it is aimed to shed light on the state-control over the people by making use of the Ottoman Archives and the memories of the travellers who visited the Ottoman Empire and aimed to give information about the travel permits and travel documents which were subject to an arrangement since the 19th century.